Semen Semenovich Zimnitsky Scientific School: Pulmonology and Cardiology - V. N. Oslopov; N. R. Khasanov; Yu. V. Oslopova; E. V. Khazova; Yu. S. Mishanina; D. V. Oslopova (Кардиоваскулярная терапия и профилактика)
Semen Semenovich Zimnitsky was a great Russian internist, a participant in the Russo-Japanese War (1904-1905). He proved that soldiers wounded by pointed bullets are seriously injured they need annual leave. S. S. Zimnitsky can be considered one of the founders of battlefield internal medicine in Russia. In the work "Diseases of the pulmonary parenchyma and pleura", he described croupous pneumonia and "abdominal syndrome" with dry pleurisy. He also concludes that pulmonary tuberculosis is not a local disease but involves the whole organism, the state of defensive mechanisms of which determines both the disease performance and the results of immunological and biological tests.The direction in internal medicine, created by S. S. Zimnitsky, was clearly reflected in following cardiology issues: heart failure, coronary artery disease, hypertension, bacterial endocarditis.